Differentiating the top English Premier League football clubs from the rest of the pack: Identifying the keys to success - Oberstone, J. (Journal of Quantitative Analysis in Sports, 2009)
This paper develops a robust, statistically significant, six independent variable multiple regression model that accounts for the relative success of English Premier League football clubs based on an array of twenty-four pitch actions collected during the 2007-2008 season (p<0.0000). Additionally, one-way ANOVA is used to identify those specific pitch actions that statistically separate the top 4 clubs from (1) the dozen clubs forming the middle of the pack and, (2) by a greater contrast, the bottom 4 clubs. Thirteen pitch actions yield statistically significant differences among these three tiers of clubs using this second method of analysis.